Comparison between two tests of delayed recall for the diagnosis of dementia - Takada Leonel Tadao; Caramelli Paulo; Fichman Helenice Charchat; Porto Cláudia Sellitto; Bahia Valéria Santoro; Anghinah Renato; Carthery-Goulart Maria Teresa; Radanovic Márcia; Smid Jerusa; Herrera Jr. Emílio; Nitrini Ricardo (Arquivos de Neuro-Psiquiatria, 2006)
Diagnosis of dementia is a challenge in populations with heterogeneous educational background. OBJECTIVE: To compare the accuracies of two delayed recall tests for the diagnosis of dementia in a community with high proportion of illiterates. METHOD: The delayed recall of a word list from the CERAD battery (DR-CERAD) was compared with the delayed recall of objects presented as line drawings from the Brief Cognitive Screening Battery (DR-BCSB) using ROC curves. Illiterate (23 controls and 17 patients with dementia) and literate individuals (28 controls and 17 patients with dementia) were evaluated in a community-dwelling Brazilian population. RESULTS: The DR-BCSB showed higher accuracy than the DR-CERAD in the illiterate (p=0.029), similar accuracy in the literate individuals (p=0.527), and a trend for higher accuracy in the entire population (p=0.084). CONCLUSION: the DR-BCSB could be an alternative for the diagnosis of dementia in populations with high proportion of illiterates.